SOUND OF “AIR BALIAN”: SEBUAH KOMPOSISI MUSIK BERDASARKAN AIR DALAM RITUAL ASEAK PENGOBATAN - Muhammad Alfath; Amor Pratama (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2021)
Music composition this sound of "Air Balian" means the sound of balian water. The word balian water refers to offerings used balian (shaman) Aseak Beubat ritual (treatment), which is in Empih Hamlet, Sumur Anyir Village, Sungai Penuh City. Basically this offering is water, with the chanting of this medium believed to be a medicine to cure pusako disease. But in fact in the life of water is not always positive, sometimes the water can destroy. The program was revealed into two musical sections namely Part I Shackled, and Part II Liberation. The musical elements of ritual mantras are used as vocabularies, and were developed with several classical music techniques (baroque-romantic) and 20-21 century music techniques. This work was played in a mix ensemble formation with music instruments violin, viola, violoncello, clarinet, triangle, shaker, tympanic, and vocal.